AVALIAÇÃO DO USO DE MEDICAMENTOS POTENCIALMENTE INAPROPRIADOS E DA ADESÃO À FARMACOTERAPIA EM IDOSOS ATENDIDOS POR UM PLANO DE SAÚDE SUPLEMENTAR - Tranhago, Camilla da Penha (2020)
The association between polypharmacy, the presence of multiple comorbidities and physiological changes related to aging increases the complexity of pharmacotherapy in the elderly. In this context, some medications may be considered inappropriate for these